SUCCESSFUL DELIVERY OF A CYCLOPIA (CEBOCEPHALUS) MONSTER IN A PLURIPAROUS CROSSBRED COW - KUMAR, SHARAD; SHARMA, UTSAV; KUMAR, SUDHIR (The Indian Journal of Animal Reproduction, 2023)
A typical case of cyclopia causing dystocia in a crossbred cow and its successful delivery is reported.